Gabriel Marcel's approach to recognizing presence: being, body, and invocation. Issue 4 (2nd October 2018) - Mullan, Margaret M.
ABSTRACT: Challenges in ascertaining human presence in technologically mediated communication invite reflection on how communicators recognize human presence. Twentieth-century French philosopher Gabriel Marcel offers insights into how human presence is felt, heard, and recognized. Marcel's texts suggest that something distinct from communication—human presence—calls one to recognize that one is with an other human person. Human presence is experienced as body and as invocation. This essay draws out ways Marcel's philosophy of body and being open up positioning, participation, and recognition of being with the other. Problems of presence present possibilities for and limitations to communication in technological settings.